2-Oxoglutarate: linking TCA cycle function with amino acid, glucosinolate, flavonoid, alkaloid, and gibberellin biosynthesis - Araújo, Wagner L.; Martins, Auxiliadora O.; Fernie, Alisdair R.; Tohge, Takayuki (Frontiers in Plant Science, 2014)
The tricarboxylic acid (TCA) cycle intermediate 2-oxoglutarate (2-OG) is used as an obligatory substrate in a range of oxidative reactions catalyzed by 2-OG-dependent dioxygenases. These enzymes are widespread in nature being involved in several important biochemical processes. We have recently demonstrated that tomato plants in which the TCA cycle enzyme 2-OG dehydrogenase (2-ODD) was antisense inhibited were characterized by early senescence and modified fruit ripening associated with differences in the levels of bioactive gibberellin (GA). Accordingly, there is now compelling evidence that the TCA cycle plays an important role in modulating the rate of flux from 2-OG to amino acid metabolism. Here we discuss recent advances in the biochemistry and molecular biology of 2-OG metabolism occurring in different biological systems indicating the importance of 2-OG and 2-OG dependent dioxygenases not only in glucosinolate, flavonoid and alkaloid metabolism but also in GA and amino acid metabolism. We additionally summarize recent findings regarding the impact of modification of 2-OG metabolism on biosynthetic pathways involving 2-ODDs.